2011
DOI: 10.1158/1078-0432.ccr-10-2441
|View full text |Cite|
|
Sign up to set email alerts
|

Dopamine Blocks Stress-Mediated Ovarian Carcinoma Growth

Abstract: Purpose Increased adrenergic activity in response to chronic stress is known to promote tumor growth by stimulating the tumor microenvironment. The focus of the current study was to determine whether dopamine, an inhibitory catecholamine, could block the effects of chronic stress on tumor growth. Experimental Design Expression of dopamine receptors (DR1-DR5) was analyzed by real time reverse transcription-PCR and by Western blotting. In vitro effects of dopamine on cell viability, apoptosis and migration wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 39 publications
3
79
0
7
Order By: Relevance
“…However, the mechanism is not resolved and it may be hypothesized that beta-blockers actually inhibit the stimulatory effect of catecholamines liberated by nerves in the tumor microenvironment. In addition, the effect of beta-blockers may also be related to the inhibition of stress, as dopamine, a stress inhibitory catecholamine has been shown to decrease ovarian cancer growth though an antiangiogenic effect (32,33). Finally, to date, only sympathetic and parasympathetic nerves have been implicated in tumor progression and the role of sensory nerves has not yet been reported.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, the mechanism is not resolved and it may be hypothesized that beta-blockers actually inhibit the stimulatory effect of catecholamines liberated by nerves in the tumor microenvironment. In addition, the effect of beta-blockers may also be related to the inhibition of stress, as dopamine, a stress inhibitory catecholamine has been shown to decrease ovarian cancer growth though an antiangiogenic effect (32,33). Finally, to date, only sympathetic and parasympathetic nerves have been implicated in tumor progression and the role of sensory nerves has not yet been reported.…”
Section: Future Directionsmentioning
confidence: 99%
“…Dopamine (DA) is an important catecholamine neurotransmitter, which exerts its function in the target organs by binding to dopamine receptors (DRs), namely DR1 and DR2 (Missale et al, 1998;Tang et al, 2013). In vitro studies have indicated that DA inhibits tumor cell proliferation in ovarian cancer and Hodgkin's lymphoma (Moreno-Smith et al, 2011;Meredith et al, 2006), but it doesn't affect colon and breast cancer cells (Sarkar et al, 2008;Moreno-Smith et al, 2013;Chakroborty et al, 2004). DA has been demonstrated to retard tumor growth by inhibiting angiogenesis in several animal models, including ovarian, gastric, breast and colon cancer (Sarkar et al, 2008;Moreno-Smith et al, 2013;Chakroborty et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine significantly inhibited cell viability and stimulated apoptosis in vitro . Moreover, dopamine reduced cyclic AMP levels and inhibited NE and VEGF-induced Src kinase activation [35]. …”
Section: Introductionmentioning
confidence: 99%